Extrusion of BMP2+ surface colonocytes promotes stromal remodeling and tissue regeneration - Julian Heuberger; Lichao Liu; Hilmar Berger; Joop van den Heuvel; Manqiang Lin; Stefanie Müllerke; Safak Bayram; Giulia Beccaceci; Hugo de Jonge; Ermanno Gherardi; Michael Sigal (Nature Communications)
Abstract The colon epithelium frequently incurs damage through toxic influences. Repair is rapid, mediated by cellular plasticity and acquisition of the highly proliferative regenerative state. However, the mechanisms that promote the regenerative state are not well understood. Here, we reveal that upon injury and subsequent inflammatory response, IFN-γ drives widespread epithelial remodeling. IFN-γ promotes rapid apoptotic extrusion of fully differentiated surface colonocytes, while simultaneously causing differentiation of crypt-base stem and progenitor cells towards a colonocyte-like lineage. However, unlike homeostatic colonocytes, these IFN-γ-induced colonocytes neither respond to nor produce BMP-2 but retain regenerative capacity. The reduction of BMP-2-producing epithelial surface cells causes a remodeling of the surrounding mesenchymal niche, inducing high expression of HGF, which promotes proliferation of the IFN-γ-induced colonocytes. This mechanism of lineage replacement and subsequent remodeling of the mesenchymal niche enables tissue-wide adaptation to injury and efficient repair.